Electrical discharge micro-texturing using compound tool electrodes for tribological and wettability applications. (3rd April 2022) - Singh, Mahavir; Tripathi, Pragya; Ramkumar, Janakarajan
ABSTRACT: The present work consists of large-area surface texturing through die-sinking electrical discharge machining (EDM) using compound tool electrodes. The compound tools were machined through the wire electrical discharge machining (WEDM). The micro-textured surfaces incorporating array of nearly square/circular-shaped micro-dimples, rectangular micro-channels and square micro-pillars were analysed for their wetting properties. An increase in water contact angle (CA) indicated higher water repellence for textured surfaces with respect to the untextured ones. Further, improved frictional behaviour was elicited through tribological analysis via the ball-on-disc test, revealing a lower average coefficient of friction (CoF) compared to the untextured surface. The wear volume of textured surfaces (micro-channels and micro-pillars) exhibited a slightly higher value with respect to the untextured surface, which can be ascribed to the stress concentration from microfeatures. However, the micro-dimpled textured surface showed a relatively lower wear volume, presenting a suitable micro-texture for improved tribological characteristics.